Detection and genotyping of cutaneous leishmaniasis species in the southeast of Iran: restriction enzyme analysis (RFLP) - Khalili M (Tehran University Medical Journal, 2009)
"n Normal 0 false false false EN-GB X-NONE AR-SA MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} Background: Leishmaniasis is a parasitic infectious disease which causes skin sores. There is no effective laboratory screening tests for leishmaniasis. Some diagnostic techniques exist that allow parasite detection and species identification by special culture and microscopy, biochemical (Isoenzymes), immunologic (immunoassays), and molecular (PCR) approaches. Specific major objectives of this study was to genotyping of Leishmania species in Bam and Shiraz city."n"n Methods: A total of 83 samples of Leishmania were collected from patients clinically suspected of cutaneous leishmaniasis. The geographic distributions of the samples were 55 samples from Bam and 28 from Shiraz city. For this propose samples of skin and bloods were blotted on filter paper. Genomic DNA extracted with a Genomic DNA extraction kit (AccuPrep, BIONEER). Aliquots of extracted DNA were kept at -20°C. region of ITS1 amplified with the published Leishmania-specific primers. 15-20mL of these amplicons, containing the amplified ITS1 region, was digested for 2h with HaeIII."n"n Results: All 55 samples from Bam were considered as L. tropica and the positive samples from Shiraz considered as L. tropica and just one sample was L. major which was belonged to a patient had previously traveled to Isfahan and Khuzestan."n"n Conclusion: In the current study a PCR technique was employed for amplification of Leishmania DNA directly in biological materials. Characterization of genus of Leishmania using RFLP-PCR method is too sensitive and too rapid, and there is no need for culturing the parasite for diagnosis.